Oral Health Promotion among Individuals with Intellectual Disabilities: A Systematic Review - AlJameel, AlBandary Hassan; Gulzar, Shabnam; Gupta, Megha; Alshehri, Alhassan Ali.; Almalki, Sultan A.; Asiri, Faris Y.; Chaudhry, Sharmeen J. (European Journal of Dentistry, 2023)
People with disabilities experience inferior health and poor access to good quality health services as compared with the general population. Optimum oral health is associated with improvement in the quality of life in such patients. As oral diseases are largely preventable, good oral health education can have a positive impact on individuals with disabilities. So, the aim of the study was to review the effectiveness of oral health promotion among individuals with intellectual disabilities (IDs). Seven electronic databases were searched using keywords like intellectual disability/mental retardation/learning disability AND dental health education/health promotion. All records that were identified electronically from this search were subjected to a preliminary review to identify eligible papers. Identified studies were grouped into oral health promotion directed at individuals with IDs, and those aimed at caregivers of people with IDs. Interpretation of the outcomes included the effects on oral health knowledge, attitudes, and behaviors (either observed or self-reported). Eventually, 16 studies were included in the review including five studies that were randomized controlled trials, while the remaining 11 studies were pre-post single group oral health promotion studies. Critical appraisal of each study was conducted with the 21-item criteria by Kay and Locker (1997) to provide a numerical quantification and ranking of the evidence. Positive changes in the behaviors and attitudes were observed, while other studies reported a considerable improvement in the knowledge of caregivers for oral healthcare of individuals with IDs. However, such activities need to be done over a long period of time with constant monitoring.
Keywords: dental health; disabilities: education; oral health; promotion